Pengaruh Customer Experience dan Customer Value terhadap Repurchase Intention melalui Customer Satisfaction pada Spotify Premium - Venessya, Jessica; Sugiyanto, Sugiyanto (Jurnal Ilmiah Manajemen Kesatuan, 2023)
Technological developments have changed the music industry, music consumption preferences have changed from purchasing physical albums to downloading digitally released music. The shift from a proprietary to a streaming-based business model is underway in various industries such as movies, games, and books. The digital music industry has already experienced a shift due to technological advances. One of the famous digital music services is Spotify. This study is to examine the effect of customer experience and customer value on repurchase intention with customer satisfaction variables as intervening variables. This type of research is quantitative research with causal relationships. Primary data was collected using the survey method by distributing questionnaires to respondents who used Spotify and then the data was processed by the path analysis method. Based on the results of research analysis, there is a direct influence between customer experience and customer value on customer satisfaction, a direct influence between customer experience and customer value on repurchase intention, a direct influence of customer satisfaction on repurchase intention, However, customer satisfaction has not been shown to be an intervening variable between customer experience and customer value to repurchase intention. Keywords : Repurchase Intention, Customer Experience, Customer Value, Customer Satisfaction, Customer Behavior